Interference with Protein Kinase C-Related Signal Transduction in Vascular Smooth Muscle Cells by Benzo[a]pyrene - Ou, X.L.; Weber, T.J.; Chapkin, R.S.; Ramos, K.S. (Archives of biochemistry and biophysics, 1995)
Elucidation of the mechanisms involved in the deregulation of vascular smooth muscle cell (SMC) growth and differentiation during the course of atherogenesis and the putative role of toxic injury in this process have been a subject of considerable interest in recent years, In this regard, we have recently shown that in vitro exposure of vascular (aortic) SMCs to benzo[a]pyrene (BaP), an atherogenic polycyclic aromatic hydrocarbon, initially delays cell cycle progression and inhibits cell proliferation and then causes permanent modulation to a highly proliferative state, To define the molecular basis of this response, we have examined critical components of the protein kinase C (PKC) signal transduction system upon exposure to BaP, Marked inhibition of serum-stimulated inositol phospholipid turnover was observed in growth-arrested SMC cultures challenged with 30 μM BaP for 24 h and then stimulated with 10% fetal bovine serum for 120 or 1800 s, Benzo[a]pyrene inhibited PKC-mediated phosphorylation of exogenous and endogenous proteins in the cytosolic and particulate fraction of cycling, as well as quiescent cultures. The PKC inhibitory response was observed as early as 0.5 h following BaP treatment and maintained for at least 5 days. Exposure of quiescent SMCs to 30 μM BaP inhibited the ability of serum to induce c-fos mRNA expression and decreased AP-1 binding to a 12-O-tetradecanoyl phorbol-13-acetate responsive element, Inhibition of PKC-related signal transduction was not due to generalized interference with cell cycle events since peak: expression of the c-myc and c-Ha-ras protooncogenes following serum stimulation of quiescent cultures was unchanged, or slightly enhanced, by 30 μM BaP. Collectively, these data suggest that the ability of BaP to modulate growth and differentiation programs in vascular SMCs involves early interference with PKC-related mitogenic signal transduction.